In-Depth Genomic and Transcriptomic Analysis of Five K+ Transporter Gene Families in Soybean Confirm Their Differential Expression for Nodulation - Rehman, Hafiz M.; Nawaz, Muhammad A.; Shah, Zahid Hussain; Daur, Ihsanullah; Khatoon, Sadia; Yang, Seung Hwan; Chung, Gyuhwa (Frontiers in Plant Science, 2017)
Plants have evolved a sophisticated network of K+ transport systems to regulate growth and development. Limited K+ resources are now forcing us to investigate how plant demand can be satisfied. To answer this complex question, we must understand the genomic and transcriptomic portfolio of K+ transporters in plants. Here, we have identified 70 putative K+ transporter genes from soybean, including 29 HAK/KT/KUP genes, 16 genes encoding voltage-gated K+ channels, 9 TPK/KCO genes, 4 HKT genes, and 12 KEA genes. To clarify the molecular evolution of each family in soybean, we analyzed their phylogeny, mode of duplication, exon structures and splice sites, and paralogs. Additionally, ortholog clustering and syntenic analysis across five other dicots further explored the evolution of these gene families and indicated that the soybean data is suitable as a model for all other legumes. Publicly available microarray data on their differential expression in nodulation was evaluated and further confirmed with the Affymetrix soybean IVT array and RNA sequencing. For each family, expression models were designed based on reads per kilobase of gene model per million mapped read (RPKM) values; the outcomes indicated differential expression linked to nodulation and confirmed the genes’ putative roles. In-depth studies such as ours provides the basis for understanding K+ inventories in all other plants.